Influences of the pH on the adsorption properties of an antimicrobial peptide on titanium surfaces - Corrales Ureña, Yendry Regina; Wittig, Linda; Vieira Nascimento, Matheus; Faccioni, Juliano Luiz; Lisboa Filho, Paulo Noronha [UNESP]; Rischka, Klaus (My University, 2015)
The adsorption behavior of the Tet-124 antimicrobial peptide and the Tet-124 peptide modified at the C- and N-terminus with the sequence glycine-3,4-dihydroxyphenylalanine-glycine (G-DOPA-G) on titanium surfaces was studied using quartz crystal micro balance with dissipation (QCM-D). At a low pH level (4.75) Tet-124 and Tet-124-G-DOPA-G form rigid layers. This is attributed to the electrostatic interactions of the positively charged lysine and arginine residues in the peptide sequence with the negatively charged titanium oxide layer. At an elevated pH level (6.9) Tet-124 shows a lower mass adsorption at the surface than Tet-124-G-DOPA-G. This is attributed to the interaction of the catechol due to the formation of complexes with the titanium oxide and titanium surface layer. The C terminal and N terminal modification with the sequence G-DOPA-G shows similar adsorption rate and mass adsorption coverage at saturation; however it is presented a more loosely layers on the G-DOPA-G-TeT-124. Fibroblast adhesion and the biocompatibility test of both the surfaces following modification with Tet-124-G-DOPA-G and the titanium alloy control showed similar results. In addition, no changes in the adhesion of E. coli bacteria due to the modification of the surface were detected.
Keywords: Titanium; Implants; Peptide; DOPA; Adsorption; Antimicrobial